Increase of High-Speed Qualities And Economic Efficiency of Use Systems of Ecological Diagnostics Diesel Engines-Microtunnels - Polivyanchuk, A. P.; Kaslin, O. I.; Skuridina, O. O. (Visnyk of V. N. Karazin Kharkiv National University. Series Еcоlogy, 2018)
Purpose. Reducing the duration and cost of procedures for environmental diagnostics of diesel power plants by increasing the speed of measurements of normalizedРM index – average operating emissions of particulate matters with exhaust gases of diesel engines. Methods. Analysis and synthesis of information, mathematical modeling, experimental studies, calculation experiment. Results.In accordance with the requirements of the international standard ISO 8178, a method of accelerated measurement (МАМ) of the PMindex is proposed, which is characterized by the maximum allowable sample filtration rate and the minimum allowable masses of particulate matter in the filters, the use of which can significantly improve the economic efficiency of applying microtunnels: with single- and multi-filter sampling methods - in 3,1 ... 4,1 times and in 5,3 ... 7,1 times, respectively. Conclusions. Compared to the most common methods of control of particulate matter emissions that are realized in mini and microtunnels of Perkins, AVL, Mitsubishicompanies, they are characterized by higher speed and economic efficiency of use - indicators that are of great importance in testing high-power diesel engines –locomotive diesel, ships and others. It is substantiated that the use of МАМ allows to shorten the duration and cost of environmental testing of mainline diesel engines - 2TE116 and shunting - TEM-2 locomotives: certification tests - by 9 ... 28%, which is 0.2 ... 0.7 h and 0, 8 ... 1,5 thousand UAH; research tests - 43 ... 53%, which is 1.7 ... 3.0 h and 4.0 ... 7.5 thousand UAH. With the reduction of the actual emission levels of particulate matter with the exhaust gases of the diesel engine, the efficiency of the use of МАМ increases.